2017
DOI: 10.5194/ars-15-77-2017
|View full text |Cite
|
Sign up to set email alerts
|

Novel post-Doppler STAP with a priori knowledge information for traffic monitoring applications: basic idea and first results

Abstract: Abstract. This paper presents a novel a priori knowledgebased algorithm for traffic monitoring applications. The powerful post-Doppler space-time adaptive processing (PD STAP) is combined with a known road network obtained from the freely available OpenStreetMap (OSM) database. The road information is applied after the PD STAP for recognizing and rejecting false detections, and moreover, for repositioning the vehicles detected in the vicinity of the roads. The algorithm presents great potential for real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…For smaller line-of-sight velocities a detection may be prevented by the presence of strong clutter. Previous studies have shown that effective clutter suppression generally is only possible when multiple receiving channels are available [17,18]. For instance, techniques like post-Doppler space-time adaptive processing (STAP) [19] effectively suppress the clutter and normalize or whiten the Doppler spectrum so that directly a single CFAR threshold can be applied once the clutter statistics are estimated.…”
Section: Principle Of the Algorithmmentioning
confidence: 99%
“…For smaller line-of-sight velocities a detection may be prevented by the presence of strong clutter. Previous studies have shown that effective clutter suppression generally is only possible when multiple receiving channels are available [17,18]. For instance, techniques like post-Doppler space-time adaptive processing (STAP) [19] effectively suppress the clutter and normalize or whiten the Doppler spectrum so that directly a single CFAR threshold can be applied once the clutter statistics are estimated.…”
Section: Principle Of the Algorithmmentioning
confidence: 99%
“…The quality of the training data impacts directly on the PD STAP performance since the CCM is used for clutter cancellation, so that this operation is of great importance. Some strategies for training data selection and update are presented and discussed in detail in da Silva et al (2019).…”
Section: Structurementioning
confidence: 99%
“…The Performance Model block provides the GMTI performance of the optimum PD STAP processor, including theoretical predictions of the detection performance, blind velocities, minimum detectable velocity (MDV), azimuth positioning error, among others. Some of the performance results were already presented in da Silva and Baumgartner (2017a) based on the framework found in Ender et al (2008).…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations